2020
DOI: 10.3390/s20174979
|View full text |Cite
|
Sign up to set email alerts
|

An Ore Image Segmentation Method Based on RDU-Net Model

Abstract: The ore fragment size on the conveyor belt of concentrators is not only the main index to verify the crushing process, but also affects the production efficiency, operation cost and even production safety of the mine. In order to get the size of ore fragments on the conveyor belt, the image segmentation method is a convenient and fast choice. However, due to the influence of dust, light and uneven color and texture, the traditional ore image segmentation methods are prone to oversegmentation and undersegmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Shubham et al [15] constructed a convolutional neural network based on Mask R-CNN [16] for predicting the size of rock fragments. Xiao et al [17] combined the residual structure of convolutional neural networks with the DUNet model [18] to propose a rock image segmentation model called RDU-Net. This model can dynamically adjust the receptive field based on the size and shape of different rock fragments.…”
Section: Computation Methods Based On the Image Modalitymentioning
confidence: 99%
“…Shubham et al [15] constructed a convolutional neural network based on Mask R-CNN [16] for predicting the size of rock fragments. Xiao et al [17] combined the residual structure of convolutional neural networks with the DUNet model [18] to propose a rock image segmentation model called RDU-Net. This model can dynamically adjust the receptive field based on the size and shape of different rock fragments.…”
Section: Computation Methods Based On the Image Modalitymentioning
confidence: 99%
“…Multiple authors have studied conveyor belt foreign body detection methods based on deep learning over the past several years.Together these studies provide important insights into precision and speed of foreign body detection. Xiao et al [10] to detect coal gangue, a human measurement model was proposed that combines the RDU-Net model with the convolutional neural network's residual structure. This model significantly increases the accuracy of image recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [ 15 ] proposed a method for detecting coal and gangue in images that uses the YOLOv3 algorithm to identify coal gangues. Xiao et al [ 16 ] suggested using a more objective approach to image segmentation based on the RDU net model, which combines the residual structure of the convolutional neural network with the dunet model. Zhang et al [ 17 ] presented a method for detecting foreign objects in coal using machine vision based on an attention neural network.…”
Section: Introductionmentioning
confidence: 99%